Guinea Pig as a Model to Study the Carotid Body Mediated Chronic Intermittent Hypoxia Effects - Docio, Inmaculada; Olea, Elena; Prieto-LLoret, Jesus; Gallego-Martin, Teresa; Obeso, Ana; Gomez-Niño, Angela; Rocher, Asuncion (Frontiers in Physiology, 2018)
Clinical and experimental evidence indicates a positive correlation between chronic intermittent hypoxia (CIH), increased carotid body (CB) chemosensitivity, enhanced sympatho-respiratory coupling and arterial hypertension and cardiovascular disease. Several groups have reported that both the afferent and efferent arms of the CB chemo-reflex are enhanced in CIH animal models through the oscillatory CB activation by recurrent hypoxia/reoxygenation episodes. Accordingly, CB ablation or denervation results in the reduction of these effects. To date, no studies have determined the effects of CIH treatment in chemo-reflex sensitization in guinea pig, a rodent with a hypofunctional CB and lacking ventilatory responses to hypoxia. We hypothesized that the lack of CB hypoxia response in guinea pig would suppress chemo-reflex sensitization and thereby would attenuate or eliminate respiratory, sympathetic and cardiovascular effects of CIH treatment. The main purpose of this study was to assess if guinea pig CB undergoes overactivation by CIH and to correlate CIH effects on CB chemoreceptors with cardiovascular and respiratory responses to hypoxia. We measured CB secretory activity, ventilatory parameters, systemic arterial pressure and sympathetic activity, basal and in response to acute hypoxia in two groups of animals: control and 30 days CIH exposed male guinea pigs. Our results indicated that CIH guinea pig CB lacks activity elicited by acute hypoxia measured as catecholamine (CA) secretory response or intracellular calcium transients. Plethysmography data showed that only severe hypoxia (7%O2) and hypercapnia (5%CO2) induced a significant increased ventilatory response in CIH animals, together with higher oxygen consumption. Therefore, CIH exposure blunted hyperventilation to hypoxia and hypercapnia normalized to oxygen consumption. Increase in plasma CA and superior cervical ganglion CA content was found, implying a CIH induced sympathetic hyperactivity. CIH promoted cardiovascular adjustments by increasing heart rate and mean arterial blood pressure without cardiac ventricle hypertrophy. In conclusion, CIH does not sensitize CB chemoreceptor response to hypoxia but promotes cardiovascular adjustments probably not mediated by the CB. Guinea pigs could represent an interesting model to elucidate the mechanisms that underlie the long term effects of CIH exposure to provide evidence for the role of the CB mediating pathological effects in sleep apnea diseases